Psychological characteristics in talented soccer players - Recommendations on how to improve coaches` assessment - Musculus, L.; Lobinger, B. H. (Frontiers in Psychology, 2018)
Psychological characteristics, including personality traits and psychological skills, have been shown to be relevant predictors of soccer performance. In research, general and sport specific standardized self-report questionnaires have been applied in psychological diagnostics of sports talent. However, with regard to the assessment of psychological characteristics of talented soccer players, a gap between research and practice is apparent. While soccer clubs often ask their coaches to assess their players on self-designed, unevaluated scouting sheets, research widely neglects expert coaches` and clubs` perspectives on relevant performance characteristics. s we believe that expert coaches` assessments could be a valid predictor of a player`s current performance and future success, we provide recommendations on how to improve coaches` assessment of psychological characteristics. As the quality of the assessment of psychological characteristics is crucial, we provide recommendations on how to ensure the central diagnostic standards: objectivity, reliability, and validity in talent assessment. Further, we argue that assessing psychological characteristics should combine self ratings of players and external ratings of coaches in talent development. Sport psychologists should assist clubs and coaches in improving the diagnostics of psychological characteristics as well as in embedding psychological diagnostics and interventions in the talent development process.